Answer :
98°
Step by step Step-by-step explanation :
As we can see in figure,
∠F = 53°
∠H = 45°
So,
![\:\mathsf{∠FGH\: +\: ∠GHF \:+ \:∠HFG\: = \:180°}](https://img.qammunity.org/2023/formulas/mathematics/college/6iu1kwwzzownkwjpklagpekpjdh7os1cb6.png)
[Angle sum property, which states that the sum of all the angles of a triangle is 180°]
=> ∠FGH + 45° + 53° = 180°
=> ∠FGH = 180° - 98°
=>
![\:\bf\boxed{∠FGH\: =\:82°}](https://img.qammunity.org/2023/formulas/mathematics/college/cfo54lf958m2p90nw8gcepf1krejvxgeeu.png)
Now,
∠x + ∠FGH = 180°
[linear pair]
=> ∠x = 180° - 82°
=>
![\:\bf\boxed{∠x\: =\:98°}](https://img.qammunity.org/2023/formulas/mathematics/college/gx2ph40owzw9y200nvi4j4yr1lxduaah03.png)
Alternative Method :
We know that sum of two opposite interior angles is equal to the exterior angle.
So
∠x = ∠GHF + ∠HFG.
=> ∠x = 45 ° + 53°
=>
![\:\bf\boxed{∠x\: =\:98°}](https://img.qammunity.org/2023/formulas/mathematics/college/gx2ph40owzw9y200nvi4j4yr1lxduaah03.png)
Hope this helps!